Analisis Akad Mukhabarah pada Perkebunan Bunga di Desa Sukajaya Kecamatan Lembang Kabupaten Bandung Barat - Annisa Nurul Fauziah; Zaini Abdul Malik; Neng Dewi Himayasari (Bandung Conference Series: Sharia Economic Law, 2024)
Abstract. Islam emphasizes the importance of muamalah in accordance with the principles of sharia taught. One important aspect of muamalah is cooperation, which can be realized in various systems such as musyarakah, mudharabah, musaqah, muzara'ah, and mukhabarah. In this research, there is a phenomenon of cooperation in Sukajaya village, Lembang subdistrict, the production sharing cooperation system in flower plantations, which is better known as paro plantation, generally uses a cooperation agreement. However, even though this collaboration was carried out verbally, it did not fully meet the requirements for cooperation. The formulation of the research problem is what the concept of mukhabarah is in Islam, what is the practice of paro cooperation in flower plantations in Sukajaya Village, and how to analyze the mukhabarah agreement on the profit sharing system. This research uses a qualitative descriptive method with a normative approach that views religion in terms of its basic and original teachings from God in which there is no human reasoning. Data was collected through interviews and observations. The research results show that the practice carried out by the community in Sukajaya Village is a cooperation system with a mukhabarah agreement. However, in practice, this collaboration is not fully in accordance with the concept taught by Islam, because there are conditions that have not been fulfilled, such as the distribution of results that is not in accordance with the initial agreement and the lack of specific time limits by the parties. Apart from that, the contract was carried out orally without any written evidence. Thus, the cooperation carried out by the community is not fully in accordance with the mukhabarah or fasid agreement. Abstrak. Islam menekankan pentingnya bermuamalah sesuai dengan prinsip-prinsip syari'ah yang diajarkan. Salah satu aspek penting dalam muamalah adalah kerjasama, yang dapat diwujudkan dalam berbagai sistem seperti musyarakah, mudharabah, musaqah, muzara'ah, dan mukhabarah. Dalam penelitian ini terjadi fenomena kerjasama di desa Sukajaya kecamatan Lembang, sistem kerjasama bagi hasil dalam perkebunan bunga, yang lebih dikenal dengan istilah paro perkebun, umumnya menggunakan akad kerjasama. Namun, kerjasama ini meskipun dilakukan secara lisan, belum sepenuhnya memenuhi syarat kerjasama. Rumusan masalah penelitian ini adalah bagaimana konsep mukhabarah dalam Islam, bagaimana praktek kerjasama paro dalam perkebunan bunga di Desa Sukajaya, serta bagaimana analisis akad mukhabarah terhadap sistem bagi hasil tersebut. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan normatif yang memandang agama dari segi ajarannya yang pokok dan asli dari Tuhan yang di dalamnya belum terdapat penalaran pemikiran manusia. Data dikumpulkan melalui wawancara, observasi. Hasil penelitian menunjukkan bahwa praktik yang dilakukan masyarakat di Desa Sukajaya adalah sistem kerjasama dengan akad mukhabarah. Namun, dalam praktiknya, kerjasama ini belum sepenuhnya sesuai dengan konsep yang diajarkan oleh Islam, karena terdapat syarat-syarat yang belum terpenuhi seperti pembagian hasil yang tidak sesuai dengan perjanjian awal dan ketidakspesifikasian batas waktu oleh para pihak. Selain itu, akad dilakukan secara lisan tanpa adanya bukti tertulis. Dengan demikian, kerjasama yang dilakukan oleh masyarakat belum sepenuhnya sesuai dengan akad mukhabarah atau fasid.